Determining Effectiveness of Monetary Transmission through Commercial Banks of Pakistan. - Badar, Munib (2024)
This study oversee the role of commercial banks of Pakistan whether effectively playing their significant role in monetary transmission. This study explores long and short-run relationships between monetary policy rate and commercial bank’s related variables and between commercial banks' related variables and macroeconomic variables. This study used quarterly data from 1998 to 2018 for the variables include central bank policy rate, Industry level data of bank deposits, bank loans and bank investments and gross domestic product. Data are collected from the official websites of the State Bank of Pakistan and tested by econometric techniques. Outcomes of this study reveal that monetary decisions influence commercial banks to some extent. However, these could not influence the economic aggregates significantly in Pakistan.